Superb microvascular imaging within intestinal ultrasonography predicts endoscopic ulcers in the terminal ileum of patients with Crohn’s disease - Masanao Nasuno; Airi Konno; Kazuki Shimoyama; Takahito Hamada; Kohei Sugiyama; Maki Miyakawa; Masanori Nojima; Hiroki Tanaka (Medicine, 2026)
This retrospective study aimed to investigate whether superb microvascular imaging (SMI) can predict endoscopic findings in the terminal ileum of patients with Crohn’s disease (CD). Patients with CD who underwent intestinal ultrasonography (IUS) between September 2020 and April 2024 and ileocolonoscopy for terminal ileum evaluation within 3 months before or after IUS were included. Those who previously underwent small bowel resection were excluded. Aplio a550 was used for IUS. SMI signals were evaluated using simplified SMI grades (0–3) and a modified Limberg score based on SMI (mLS-SMI, 0–4). Endoscopic findings were categorized as no, aphthous, small, or large ulcer. The proportion of patients with each endoscopic finding was determined according to mLS-SMI and SMI grades. Furthermore, the sensitivity and specificity of each grade for predicting corresponding endoscopic findings were compared. In total, 204 patients were included, with 96, 68, 25, and 15 having no, aphthous, small, and large ulcers, respectively. Additionally, 161, 14, 13, 11, and 5 patients had mLS-SMI grades 0, 1, 2, 3, and 4, while 157, 27, 12, and 8 patients had SMI grades 0, 1, 2, and 3, respectively. As the mLS-SMI and SMI grades increased, the proportion of patients with aphthous, small, or large ulcers also increased. Likewise, the proportion of patients with small or large ulcers increased. The sensitivity and specificity for predicting aphthous, small, or large ulcers were 24% and 97% for mLS-SMI grade ≥2, and 37% and 93% for SMI grade ≥1, respectively. For predicting small or large ulcers, they were 50% and 95% for mLS-SMI grade ≥2, and 70% and 88% for SMI grade ≥1, respectively. SMI grade ≥ 1 offered a significantly higher sensitivity for predicting small or large ulcers than mLS-SMI grade ≥ 2 ( P = .008). Higher mLS-SMI and SMI grades corresponded to an increased prevalence of endoscopic ulcers. Therefore, SMI grading may provide additional information for evaluating ulcerative lesions in patients with CD.